Testing The Information System Success Models Through Myob Accounting Software - Septian Bayu Kristanto; Herni Kurniawati (Perspektif Akuntansi, 2020)
The purpose of this study wants to test the Information System Succes Model through Accounting Software. The test examines the effect of System Quality to Service Quality, the effect of System Quality to Work performance, and the effect of Service Quality to Work Performance. The object in this research is MYOB accounting software. The data gathered with questionnaires in 2 types, paper and online. From 500 questionnaires are distributed, 315 was returned. It consists of 194 respondents through online, and 116 respondents through the paper. The obtained data were analyzed using Structural Equation Modelling. The result of data analysis showed that the System Quality has a positive significant effect on the Service Quality, Service Quality has a positive significant effect on Work Performance, and System Quality have a positive significant effect on Work Performance. The overall result indicates that MYOB accounting software has good quality and related to user performance. Specifically, the user refers to the basic user, which is a university student.